Study of the mechanism of digitalization boosting urban low-carbon transformation - Xinfa, Tang; Jinglin, Li (Frontiers in Environmental Science, 2022)
The climate problem is severe and many urban climates are poor. To deal with a series of climate problems, low-carbon measures are indispensable. Digital development is becoming a new driving force for social development. Therefore, the development of urban low-carbon transformation should be based on digital construction. This paper explores the significance and theoretical mechanism of the research of the mechanism of digitalization boosting urban low-carbon transition. Theoretically, digitalization can reduce carbon emissions through mechanisms such as optimizing industrial structure, adjusting energy structure, improving government governance efficiency, and changing people’s way of production and life. Finally, from the perspective of carbon neutrality, this paper puts forward relevant countermeasures, from the following six aspects: building a carbon emission measurement and monitoring system, promoting the digital transformation of enterprises, increasing the research and development of new energy technologies, improving the carbon emission market trading system, optimizing the carbon emission administrative management system, and practicing the low-carbon concept.